Acculturation, self‐construal, mental and physical health: An explorative study of East Asian students in Germany. (11th November 2013) - Shim, Gayoung; Freund, Henning; Stopsack, Malte; Kämmerer, Annette; Barnow, Sven
<x xml:space="preserve">Abstract</x> The present study explores acculturation and its associated aspects of two East Asian student groups with different levels of exposure to German culture (100 international students from East Asian countries [IS]; 61 second generation students of East Asian descent [SGS]). First, we investigated the relationships between acculturation, self‐construal, depressive and somatic symptoms, and differences between the student groups in these variables. Second, the four acculturation types (integration, assimilation, separation and marginalization) were examined regarding their relationship to self‐construal and health outcomes. The results showed that the acculturation dimensions (mainstream, heritage) were relevant to the level of depressive symptoms for IS which was not the case for SGS. Furthermore, IS reported more somatic symptoms whereas there was no difference between the two groups in the level of depressive symptoms. In the analysis of acculturation types, assimilated and integrated students were characterized by high independent self‐construal, while separated and integrated students showed high interdependent self‐construal. Assimilated students displayed the least depressive symptoms of all acculturation groups. This study highlights different characteristics of East Asian students in acculturation, self‐construal and health outcomes, and discusses the complexity of the relationships between acculturation types and health.